HUBUNGAN PENERAPAN AUTOLISIS MENGGUNAKAN NaCL DENGAN PENYEMBUHAN LUKA PADA PASIEN KRONIS: DIABETES MELITUS DI MURNI TEGUH MEMORIAL HOSPITAL - Frisca Mawarni Medrofa (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2025)
Chronic wounds are wounds in the perfect healing period or recurring wounds for more than two weeks. Things that need to be considered in wound healing are tissue debridement if the tissue is no longer viable, treating infections by controlling bacterial humidity, and maintaining fluid balance by managing exudates, as well as choosing the right dressing. The debridement process is the treatment of damaged wound tissue. Debridement removes necrotic tissue and heavily contaminated tissue, thereby speeding up the wound healing process and preventing infection. The classification of debridement includes surgical debridement, autolysis debridement, medical debridement, biological debridement, and surgical debridement. This type of autolysis wound dressing is a dressing that functions as an autolytic cleaner and removes dead tissue such as necrotic tissue. One of the dressings chosen to help the body cleanse is a dressing using NaCl. NaCl 0.9% is a physiological fluid which has a very adequate body salt content making it suitable for wound care. This research uses quantitative research methods using a correlational design. Sampling used total sampling with a total sample of 11 respondents. The research instrument used was a questionnaire sheet. The data analysis used was the Pearson Correlation test. The results of the study show that there is a relationship between the application of autolysis using NaCl and wound healing in chronic patients: diabetes mellitus at Murni Teguh Memorial Hospital. The Pearson correlation test shows a p value of 0.043 (<0.05). There is a relationship between the application of autolysis using NaCl and wound healing in chronic patients: diabetes mellitus at Murni Teguh Memorial Hospital.